Une littérature en dépendances. La littérature de langue bretonne, 2000-2010 - Mannaig Thomas (La Bretagne Linguistique, 2014)
The promotion of Breton-language literature is presented as one of the language policy areas developed by the regional authority to support the languages of Brittany. It has decided to act in this literary space by taking responsibility for a significant part of the funding of literary works. While Breton literature does not constitute a ‘field’ in the Bourdieusian sense because it is not autonomous, it is still necessary to analyse this space and its actors for a better understanding of its functioning, its various dependencies and the reasons for its heteronomy. This article presents an overview of the Breton literature publishing situation in the period 2000-2010 and highlights the main characteristics and forces acting on this literary space in order to explain why literature is just one element of a more global issue.